Bedbug - Reinhardt, Klaus (Animal, 2018)
Few animals elicit such a profoundly honest response of horror, fear and fright as the bedbug. Uninvited, bedbugs invade your privacy; they enter your bed, leave their marks and take away your bodily fluid - blood. From fossils to ancient Greek theatre, modern horror fiction and the bitter battles of recent scientific research, Bedbug investigates the animal's natural history and examines how ordinary people, travellers, artists and scientists have experienced and confronted bedbugs over the centuries. Klaus Reinhardt explores how the fear of bedbugs has been institutionalized, leading not only to the development of pest control and research laboratories but to bedbugs becoming the Other, used to represent personal enemies, denigrate social classes and characterize capitalist villains. With a mix of amusing, repulsive and illuminating illustrations, Bedbug informs, entertains and even pledges for tolerance for a surprising and profoundly misunderstood insect.
Keywords: Bedbugs; luteet; syöpäläiset; kulttuurihistoria; mielikuvat; torjunta; toiseus; skinnbaggar; ohyra; bekämpning; kulturhistoria; föreställningar (uppfattningar); främmandeskap